THE DIVERSITY OF SMALL MAMMALS AT THE BUFFER ZONE OF MOUNT SLAMET, CENTRAL JAVA - Maharadatunkamsi Maharadatunkamsi (Masyarakat Zoologi Indonesia, 2014)
Â A study was conducted by a combination of collecting the animals and direct observation in order to define small mammals community in surrounding buffer zone of Mount Slamet at Curug Cipendok and Banjarsari. The small mammals community at the surveyed areas was described by using Shannon- Wiener index of diversity and Simpson index of dominance. Results indicating that Curug Cipendok had higher small mammals diversity and lower level of dominance of certain species compare to Banjarsari.